Sistemas de produção de feno de capim tifton 85 no inverno - Ames, João Paulo (2012)
We carried out two experiments in order to evaluate the production of Tifton 85 hay in winter. The first experiment evaluated the use of chemical nitrogen fertilizer, use of pig slurry, the association with Tifton 85 and Tifton 85 single pea without the application of fertilizer on structural characteristics, dry matter production, rate of dehydration, nutritional value and occurrence of fungi in Tifton 85 and its association. In the evaluation of the drying curves the experimental design occurred in randomized blocks with sub plots divided by time taking into consideration 4 management systems and 8 sampling times (from cutting up to baling), with 5 repetitions. In the bromatologicalcompositionthe experimental designtook into consideration treatments 4, 3 sampling times (cutting, baling and storage) were studied with 5 repetitions. In the quantification and identification of fungi 4 management systems 2 times evaluation (cutting and after storage) in a randomized complete block design with sub plots divided by time, with 5 repetitions. The second experiment was divided into two stages: in the first one it was evaluated the oversownof the Guapas white oat, with IPR126white oat and Tifton 85 single with chemical nitrogen fertilizer on the structural characteristics, dry matter yield, nutritional value, dehydration curve, occurrence of fungi in Tifton 85 grass). The MS experimental designoccurredthrough randomized blocks with 3 treatments and 5 repetitions. The dehydration curve was evaluated in a randomized complete block design with sub plots divided into time, taking into consideration: 3 treatments, 8 sampling times (cutting up to baling), with 5 repetitions. For nutritional value and occurrence of fungi in the experimental design was randomized blocks with sub plots being divided in time 3 treatments, 2-cycle assessment (cut and after storage for 30 days) with 5 repetitions. A second experiment was conducted which aimed to evaluate the oversown use of white oats IPR 126 and Guap, pea, the use of swine manure and chemical fertilizer nitrogen application on soil physical properties (resistance to penetration, total porosity, macroporosity and microporosity) in a randomized block design in split-plot treatments subdivided into 5 management systems, 2 depths evaluation (0-5cm and 6-10 cm) and 5 repetitions